Federalism: Prerequisite for Effective Criminal Justice Administration in the States - Okoeguale, Hilary (ABUAD Law Journal, 2019)
The Federal system being practiced in Nigeria has been widely criticized and referred to as asymmetrical in favour of the Federal Government. In the Context of the criminal justice system (CJS), twoprincipalagencies are in the Exclusive Legislative list, that is to say, the Nigeria Police Force and the Nigerian Correctional Service. This situation leaves the States short of the requisite resources for effective criminal justice administration. This paper examines the federal structure as designed by the extant Constitution of the Federal Republic of Nigeria 1999 (as amended) (CFRN) with a view to bringing to the fore, the extent to which State Governments in Nigeria can maintain a coherent and smooth criminal justice administration. The paper also interrogates the capacity of State Governmentsto fight crime given the resources at their disposal. In doing so, it examines the tenets of a federal system of government and the extent of compliance in Nigeria. Consequently, it was found that theCFRN, robs State Governments in Nigeria of the requisite authority to maintain an independent, autonomousand effective criminal justice system. In other words, State Governments in Nigeria could make laws which a federal Police Force may refuseto carry out. This has negative implications for the state administration of justice, especially in the face of the upsurge in crime rate in Nigeria. Thepaper concludes that a State would be inherently weak if it were incapacitated or unable to enforce its own laws and as such recommends that the CFRN be reviewed in order to allow for a State Police Force and State Correctional Service.